Cloning and sequencing of the immunoglobulin A1 protease gene (iga) of Haemophilus influenzae serotype b. - Poulsen, K (1989)
Secretion of immunoglobulin A1 (IgA1) proteases is a characteristic of Haemophilus influenzae and several other bacterial pathogens causing infectious diseases, including meningitis. Indirect evidence suggests that the proteases are important virulence factors. In this study, we cloned the iga gene encoding immunoglobulin A1 (IgA1) protease from H. influenzae serotype b into Escherichia coli, in which the recombinant H. influenzae iga gene was expressed and the resulting protease was secreted. Sequencing a part of a 7.5-kilobase DNA fragment containing the iga gene revealed a large open reading frame with a strongly biased codon usage and having the potential of encoding a protein of 1,541 amino acids and a molecular mass of 169 kilodaltons. Putative promoter and terminator elements flanking the open reading frame were identified. Comparison of the deduced amino acid sequence of this H. influenzae IgA1 protease with that of a similar protease from Neisseria gonorrhoeae revealed several domains with a high degree of homology. Analogous to mechanisms known from the N. gonorrhoeae IgA protease secretion, we propose a scheme of posttranslational modifications of the H. influenzae IgA1 protease precursor, leading to a secreted protease with a molecular mass of 108 kilodaltons, which is close to the 100 kilodaltons reported for the mature IgA1 protease.